High precision calculations within the MSSM - Mihaila, Luminita (Nuclear physics. Proceedings supplements, 2008)
In this talk we report on two recent high precision calculations within the minimal supersymmetric extension of the Standard Model. In the first part of the talk we present the computation of the light CP-even Higgs boson mass with three-loop accuracy, taking into account the next-to-next-to-leading order effects from supersymmetric Quantum Chromodynamics. Furthermore, we discuss a consistent evolution of the strong coupling constant αs from MZ to the GUT scale, involving three-loop running and two-loop decoupling. For both observables the numerical results amount to corrections of the same order as the current experimental accuracy or that expected at the CERN Large Hadron Collider (LHC).